EARLY POSTOPERATIVE COMPLICATIONS IN ROUX-EN-Y GASTRIC BYPASS - STOLL,Aluisio (2016)
ABSTRACT Background: Roux-en-Y gastric bypass is one of the most common bariatric surgery and leads to considerable weight loss in the first months. Aim: To quantify the main early postoperative complications in patients submitted to the gastric bypass. Method: Observational retrospective cohort. Data of 1051 patients with class II obesity associated with comorbidities or class III obesity submitted to the gastric bypass with 30 days of follow-up starting from the date of the surgery. Results: The age average was 36 years with a predominance of females (81.1%). The mean preoperative body mass index was 43 kg/m². The major complication was fistula (2.3%), followed by intestinal obstruction (0.5%) and pulmonary embolism (0.5%). Death occurred in 0.6% of the cases. Conclusion: In the period of 30 days after surgery the overall complication rate was 3.8%; reoperation was necessary in 2.6% and death occurred in 0.6%. Fistula was the main complication and the leading cause of hospitalization in intensive care unit, reoperation and death.